1992
DOI: 10.1258/002367792780740503
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intracage ventilation on micro environmental conditions in filter-top cages

Abstract: Filter-top cages, while effective in reducing cross contamination by particulate material including microbes, can also cause accumulation of the waste gases carbon dioxide and ammonia as well as increased intracage relative humidity. A prototype system which provided each cage with 23 air changes per hour through a nozzle inserted in the filter lid was evaluated. The ventilated cageing system was effective in reducing intracage carbon dioxide, ammonia and relative humidity levels. Mean weekly carbon dioxide le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Πρέπει να υπάρχει αρκετός χώρος μεταξύ του υψηλότερου ση μείου του σώματος και της οροφής του κλωβού, τόσο για τον απαιτούμενο αερισμό όσο και για την αποφυ γή τραυματισμών. Ας σημειωθεί ότι κατά τη χρήση κλωβών με φίλτρα, υφίσταται μείωση του αερισμού μέ χρι και κατά 70%, αύξηση του επιπέδου συγκέντρωσης αμμωνίας και διοξειδίου του άνθρακα και αύξηση της σχετικής υγρασίας και της εσωτερικής θερμοκρασίας του κλωβού* αυτό αντιμετωπίζεται με μείωση του αριθ μού των ζώων που θα τοποθετηθούν εντός αυτοΰ (Lipman et al 1992, LABA/LASA Working Group 1993, Swallow et al 2005). …”
Section: α) μεταφοραunclassified
“…Πρέπει να υπάρχει αρκετός χώρος μεταξύ του υψηλότερου ση μείου του σώματος και της οροφής του κλωβού, τόσο για τον απαιτούμενο αερισμό όσο και για την αποφυ γή τραυματισμών. Ας σημειωθεί ότι κατά τη χρήση κλωβών με φίλτρα, υφίσταται μείωση του αερισμού μέ χρι και κατά 70%, αύξηση του επιπέδου συγκέντρωσης αμμωνίας και διοξειδίου του άνθρακα και αύξηση της σχετικής υγρασίας και της εσωτερικής θερμοκρασίας του κλωβού* αυτό αντιμετωπίζεται με μείωση του αριθ μού των ζώων που θα τοποθετηθούν εντός αυτοΰ (Lipman et al 1992, LABA/LASA Working Group 1993, Swallow et al 2005). …”
Section: α) μεταφοραunclassified
“…Allergen containment aside, filter tops can significantly affect cage ventilation performance and the cage microenvironment in terms of carbon dioxide and ammonia concentrations and relative humidity (Baer et al 1997;Lipman 1992Lipman , 1999Lipman et al 1992;Memarzadeh 1998; al. 1997).…”
Section: Isolation or Enclosurementioning
confidence: 99%
“…Although MIS are effective for prevention of inter-cage transmission of microorganisms [5], it has been suggested that they reduce intra-cage ventilation [12], thus causing deterioration of the physical environment through accumulation of moisture, carbon dioxide, ammonia, and heat [3,4,14,22,25]. For this reason, Keller et al [11], Wu et al [25] and Lipman et al [14] added forcedair ventilation to the MIS to improve the intra-cage environment, and demonstrated that forced-air ventilation could limit the increase in ammonia concentration to a great extent. In another advance, Kurosawa et al developed a forced-air-ventilated micro-isolation system (FVMIS) for the purpose of directly controlling the climatologic, physical, chemical and biological factors of the microenvironment of rodent cages [13].…”
Section: Introductionmentioning
confidence: 99%